Trends in gender disparities at the transition from school to work : labour market entries of young men and women between 1984 and 2005 in West Germany - Jacob, Marita [Verfasser]; Kleinert, Corinna [Verfasser]; Kühhirt, Michael [Verfasser] (My University, 2013)
"This paper examines trends in school-to-work transitions of young men and women with lower and higher secondary education in West Germany between 1984 and 2005. This period was marked by an increase in young women’s educational attainment and a continuous growth of the service sector. We assume that both developments have benefited women more than men in terms of smooth labour market integration. Results from discrete event history analyses show that in recent years women indeed found their first job faster than men. However, this is not mainly due to an improvement in young women’s chances to enter employment, but to deteriorating employment prospects of men, in particular of unskilled men." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.2.2.1 Erste Schwelle, in Ausbildung; G 2.4.5 Gender Mainstreaming; T 1.2 Historische Berufsbildungsforschung; I 2.1.2 Alte Bundesländer; Berufseinmündung; Erste Schwelle; Gender Mainstreaming; Historische Entwicklung; Quantitative Angaben; 1984-2005; Westdeutschland